2013
DOI: 10.1016/j.tjog.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The fertility quality of life (FertiQoL) questionnaire in Taiwanese infertile couples

Abstract: The results of this study provide a baseline QoL in infertile couples in Taiwan, and could potentially be used as a guide for clinical counseling and future works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 15 publications
4
54
4
1
Order By: Relevance
“…This same present study result agrees with the results of at least three other researches. (47,48,49) On the other hand, this result contradicts the results of at least four other studies: First, Parnian R et al (2017) (50) who found that the infertile women had better quality of life, with total mean score 88.22±13.75. They add that there was no statistically significant differences in the total mean score of quality of life between fertile and infertile women.…”
Section: Coping Strategies and Quality Of Life Among Infertile Women mentioning
confidence: 54%
“…This same present study result agrees with the results of at least three other researches. (47,48,49) On the other hand, this result contradicts the results of at least four other studies: First, Parnian R et al (2017) (50) who found that the infertile women had better quality of life, with total mean score 88.22±13.75. They add that there was no statistically significant differences in the total mean score of quality of life between fertile and infertile women.…”
Section: Coping Strategies and Quality Of Life Among Infertile Women mentioning
confidence: 54%
“…The FertiQoL mean scores of the participants with the female and male factors were 74.7 ± 10.3 and 64.5 ± 12.3, respectively, which were significantly different. In previous studies, the FertiQoL scores for infertile partners (mostly male partners) were 80.0 (Huppelschoten et al , ), 60.6 (Hsu, Lin, Hwang, Lee, & Wu, ), and 83.3 ± 10.8 (Santoro et al , ). The FertiQoL scores that were reported in Japan were lower than those reported in other countries.…”
Section: Discussionmentioning
confidence: 92%
“…Patients who enrolled in the study signed a consent form and were asked to complete a background information questionnaire and four additional questionnaires (standardized measures used to assess emotional functioning) each at two separate time points: one before and one after completing the Yoga workshop: (i) The fertility-related quality of life tool (FertiQoL), which has been shown to be a valid tool to assess quality of life among women with infertility (Aarts et al, 2011;Boivin et al, 2011;Hsu et al, 2013); (ii) the Dyadic Adjustment Scale (DAS), a measure of couple adjustment; (iii) Spielberger State-Trait Anxiety Inventory (STAI) (Spielberger et al, 1983); and (iv) the Beck Depression Inventory (BDI) (Beck et al, 1961(Beck et al, , 1988. As Montreal is a bilingual city, the questionnaires were available in English or French according to patient preference.…”
Section: Participantsmentioning
confidence: 99%